2017
DOI: 10.1021/acs.jmedchem.6b01594
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Synthesis of a Phosphoramidate Prodrug of a Pyrrolo[2,1-f][triazin-4-amino] Adenine C-Nucleoside (GS-5734) for the Treatment of Ebola and Emerging Viruses

Abstract: The recent Ebola virus (EBOV) outbreak in West Africa was the largest recorded in history with over 28,000 cases, resulting in >11,000 deaths including >500 healthcare workers. A focused screening and lead optimization effort identified 4b (GS-5734) with anti-EBOV EC 50 = 86 nM in macrophages as the clinical candidate. Structure activity relationships established that the 1′-CN group and C-linked nucleobase were critical for optimal anti-EBOV potency and selectivity against host polymerases. A robust diastereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
575
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 591 publications
(595 citation statements)
references
References 36 publications
10
575
0
10
Order By: Relevance
“…One study reported the compassionate use of GS-5734 in combination with ZMapp and a convalescent buffy coat transfusion in a newborn baby who survived EBOV infection 177 . GS-5734 is currently being used in West Africa in a trial called PREVAIL for men with persistent EBOV RNA in semen 178 .…”
Section: Gs-5734mentioning
confidence: 99%
“…One study reported the compassionate use of GS-5734 in combination with ZMapp and a convalescent buffy coat transfusion in a newborn baby who survived EBOV infection 177 . GS-5734 is currently being used in West Africa in a trial called PREVAIL for men with persistent EBOV RNA in semen 178 .…”
Section: Gs-5734mentioning
confidence: 99%
“…For the RdRp target in the genus Betacornavirus, there are several potential drugs or compounds, including favipiravir, ribavirin, penciclovir, galidesivir, remdesivir, 6'-fluorinatedaristeromycin analogs, and acyclovir fleximer analogs [12]. Remdesivir (GS-5734), the phosphoramidate prodrug of an adenosine C-nucleoside [13], has a structure similar to tenofovir alafenamide, which is a nucleotide analog of adenosine 5-monophosphate with antiviral activity against hepatitis B virus and human immunodeficiency virus. It was developed by Gilead Science Inc. and has not been licensed or approved anywhere for now.…”
Section: Rna Polymerasesmentioning
confidence: 99%
“…GS-441524 is also a broad-spectrum inhibitor of a variety of RNA viruses from four families (Filoviridae, Flaviviridae, Paramyxoviridae, and Pneumoviridae), including HCV and RSV. 163,164 However, the addition of a 2 0 -C-methyl group, as in the case of the GS-6620, 165,166 significantly reduces the antiviral spectrum to HCV only. The relatively weak antiviral activity of GS-441524 across all viruses (0.5-50 mM EC 50 ) was attributed to its inefficient intracellular phosphorylation, which could be improved by adding a monophosphate prodrug to the parent nucleoside.…”
Section: Gs-5734 For Ebola Virus and Covmentioning
confidence: 99%